Ginsenoside Rb1 increases insulin sensitivity by activating AMP‐activated protein kinase in male rats. Issue 9 (9th September 2015) - Shen, Ling; Haas, Michael; Wang, David Q.‐H.; May, Aaron; Lo, Chunmin C.; Obici, Silvana; Tso, Patrick; Woods, Stephen C.; Liu, Min
Abstract Although ginseng has been reported to ameliorate hyperglycemia in animal models and clinical studies, the molecular mechanisms are largely unknown. We previously reported that chronic treatment with ginsenoside Rb1 (Rb1), a major component of ginseng, significantly reduced fasting glucose and improved glucose tolerance in high‐fat diet (HFD)‐induced obese rats. These effects were greater than those observed in pair‐fed rats, suggesting a direct effect of Rb1 on glucose homeostasis, and this possibility was confirmed in the present study. In lean rats fed standard rodent chow, 5‐day treatment with Rb1 significantly improved glucose tolerance and enhanced insulin sensitivity. Notably, those effects were not accompanied by reduced food intake or changed body weight. To elucidate the underlying molecular mechanisms, rats fed a HFD for 4 weeks were treated with Rb1 for 5 days. Subsequently, euglycemic‐hyperinsulinemic clamp studies found that compared to vehicle, Rb1, while not changing food intake or body weight, significantly increased glucose infusion rate required to maintain euglycemia. Consistent with this, insulin‐induced inhibition of hepatic gluconeogenesis was significantly enhanced and hepatic phosphoenolpyruvate carboxykinase and glucose‐6‐phosphatase gene expression was suppressed. Additionally, glucose uptake was significantly increased in skeletal muscle. While proximal insulin signaling was not changed after Rb1 treatment, increased phosphorylation of TBC1D4, a downstream target of AMPK signaling, appears to be a key part of the mechanism for Rb1‐stimulated glucose uptake in skeletal muscle. These findings indicate that Rb1 has multiple effects on glucose homeostasis, and provide strong rationale for further evaluation of its potential therapeutic role.